Intrathecal and systemic alterations of L-arginine metabolism in patients after intracerebral hemorrhage. Issue 8 (August 2021) - Mader, Marius M; Böger, Rainer; Appel, Daniel; Schwedhelm, Edzard; Haddad, Munif; Mohme, Malte; Lamszus, Katrin; Westphal, Manfred; Czorlich, Patrick; Hannemann, Juliane
Alterations in the concentration of nitric oxide (NO) and L-arginine metabolites have been associated with the pathophysiology of different vascular diseases. Here, we describe striking changes in L-arginine metabolism after hemorrhagic stroke. Blood and cerebrospinal fluid (CSF) samples of patients with intracerebral hemorrhage (ICH) and/or intraventricular hemorrhage were collected over a ten-day period. Liquid chromatography-tandem mass spectrometry was used to quantify key substrates and products of L-arginine metabolizing enzymes as well as asymmetric (ADMA) and symmetric dimethylarginine (SDMA). Changes in the plasma were limited to early reductions in L-ornithine, L-lysine, and L-citrulline concentrations. Intrathecally, we observed signs of early NO synthase (NOS) upregulation followed by a decrease back to baseline accompanied by a rise in the level of its endogenous NOS-inhibitor ADMA. SDMA demonstrated increased levels throughout the observation period. For arginase, a pattern of persistently elevated activity was measured and arginine:glycine amidinotransferase (AGAT) appeared to be reduced in its activity at later time points. An early reduction in CSF L-arginine concentration was an independent risk factor for poor outcome. Together, these findings further elucidate pathophysiological mechanisms after ICH potentially involved in secondary brain injury and may reveal novel therapeutic targets.